Aerodynamics of bicycles
Introduction - Adding Wind Speeds and Directions - Characteristics of Fluids - Pressure - Continuity Equation - Bernoulli's Equation - Streamlines and Streamtubes - Transition and Turbulence - Separation - Drag of Blunt Bodies and Streamlined Bodies - Golf Balls, Cricket Balls and Tennis Balls - Lift and Stall